Pengembangan Bahan Ajar Mata Kuliah Belajar Dan Pembelajaran Berbasis Tri Ciri Tentara Pelajar (Patriotisme, Kepeloporan Dan Kemandirian) Pada Mahasiswa UTP Surakarta - Beny Asfuri, Ninda; Ambarsari, Rika Yuni (Universitas Nusantara PGRI Kediri, 2021)
Teaching materials are one of the important factors in the effectiveness of learning, especially at the Higher Education level. Lack of teaching materials can certainly affect the quality of learning or lectures. The purpose of developing this module is 1) to increase students' understanding of the three characteristics of student soldiers which will be developed in learning courses so that students really animate, interpret and can implement them in everyday life on campus and outside campus, ) to determine the feasibility level of the developed teaching materials. This type of research is research and development research. Development refers to the ADDIE development model (analysis, design, development, implementation and evaluation). Based on the overall product assessment by material and learning experts, a score of X = 265 was obtained, which was included in the